Pengembangan Strategi Industri Kreatif Menghadapi Persaingan (Studi kasus: Sangkar Burung Kecamatan Jebres) - Nurseto, Bayu; , Etika Muslimah, S.T., M.M., M.T; , Dr. Suranto (2015)
Creative industry as an industry that derived from the utilization of creativity , individual skills and talent of welfare and to create jobs through the creation of power resources and utilization of creation and copyright .A cage of a bird are industry handicrafts which power the bomber was mengandalankan creation .The purpose of this research to find out the development of industrial strategy of cage birds by identifying assess internal and external factors in the environment can affect to companies .The tujyan was able to know the development of research strategy , and knowing chances , the threat of , weakness , of the force in the industry .In this study using analysis ( strength training , weakness , opportunity , treath ) .Training analysis is able to do that be a strength , weakness , opportunities , the threat of .Objectives in this study in order to compete with other industry as well as a competitor who can provide economic contributtion